New species of Edessa Fabricius, 1803 (Hemiptera: Pentatomidae) from Costa Rica - Fernandes, Jose Antonio Marin; Silva, Valeria Juliete Da; Correia, Andre Oliveira; Nunes, Benedito Mendes (Zootaxa, 2015)
The edessines from Costa Rica are little known; only 18 species have been registered or described from this country so far. Mainly based in a large sample from Instituto Nacional de Biodiverdidad (INBio), Costa Rica, we decided to update the information concerning Edessinae from Costa Rica. We present a list of species from Costa Rica raising the number of known species from Costa Rica to 65. We are also describing nine new species: Edessa bella Fernandes & Silva, E. bruneolineata Fernandes & Correia, E. curvata Fernandes & Nunes, E. lewisi Fernandes & Silva, E. nigroangulata Fernandes & Silva, E. osae Fernandes & Nunes, E. oxcarti Fernandes & Correia, E. pallidoangulata Fernandes & Nunes and E. puravida Fernandes & Correia. Species were described, illustrated and photographed. Distribution maps for the species are also provided.